2020
DOI: 10.1007/s10539-020-09763-1
|View full text |Cite
|
Sign up to set email alerts
|

Chimpanzee normativity: evidence and objections

Abstract: This paper considers the question of whether chimpanzees possess at least a primitive sense of normativity: i.e., some ability to internalize and enforce social norms-rules governing appropriate and inappropriate behaviour-within their social groups, and to make evaluations of others' behaviour in light of such norms. A number of scientists and philosophers have argued that such a sense of normativity does exist in chimpanzees and in several other non-human primate and mammalian species. However, the dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 91 publications
0
20
0
2
Order By: Relevance
“…However, the lack of consensus regarding the core psychological properties of social norms in humans has meant that claims about animal normativity are subject to shifting standards of evaluation. As Laura Danón (2019) has noted, there are at least three distinct conceptions of norms employed in these debates: minimal accounts, which require only an affectively based sense of social appropriateness (Andrews 2020); robust ought-thoughts, which require explicit and intrinsically motivational representations of rules (Fitzpatrick 2020); and reflective accounts, which additionally require an explicit conception of norms as such (Korsgaard 2006); Tomasello's shared intentionality account of normativity, which treats norms as the product of a form of collective, group-level intentionality, may be a fourth (Tomasello 2019).…”
Section: Methodological Pluralismmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the lack of consensus regarding the core psychological properties of social norms in humans has meant that claims about animal normativity are subject to shifting standards of evaluation. As Laura Danón (2019) has noted, there are at least three distinct conceptions of norms employed in these debates: minimal accounts, which require only an affectively based sense of social appropriateness (Andrews 2020); robust ought-thoughts, which require explicit and intrinsically motivational representations of rules (Fitzpatrick 2020); and reflective accounts, which additionally require an explicit conception of norms as such (Korsgaard 2006); Tomasello's shared intentionality account of normativity, which treats norms as the product of a form of collective, group-level intentionality, may be a fourth (Tomasello 2019).…”
Section: Methodological Pluralismmentioning
confidence: 99%
“…For example, Laura Schlingoff and Richard Moore -who define norms in terms of explicit representations of rules -have argued that all of the chimpanzee behaviors that theorists have described as social norms can be more parsimoniously explained by lowerlevel cognitive processes, without appeal to representations of normative rules (Schlingloff and Moore 2017). For proponents of rule-based approaches to animal norms, such as Laura Danón (2019) and Simon Fitzpatrick (2020), addressing this challenge would mean developing a research program that could systematically test all the predictions of a particular normative rule, thereby eliminating all the lower-level, non-rule-based explanations of the normative behavior in question. Such a research program would need to proceed in the same manner as research on altruistic explanations of spontaneous helping behavior, which involved the systematic elimination of alternative, egoistic explanations (Batson et al 1988).…”
Section: Methodological Pluralismmentioning
confidence: 99%
See 1 more Smart Citation
“…About 15 years ago, scholars interested in human evolution -anthropologists, biologists, economists, philosophers, and (a few) psychologists -began to use 'norm psychology' (or 'normative cognition') to refer to a set of cognitive and motivational mechanisms that, they believe, have been specialised by genetic evolution for processing social 'rules' or 'behavioural standards' (e.g. Boyd & Richerson 2005;Chudek & Henrich 2011;Fehr & Schurtenberger 2018;Fitzpatrick 2020;Henrich 2020;Henrich & Muthukrishna 2021;House 2018;House et al 2020;Kelly & Davis 2018;Mikhail 2011;O'Neill & Machery 2018;Richersen et al 2016;Sripada & Stich 2006;Zefferman 2014). 'Norm psychologists', whatever their disciplinary affiliation, believe that the mental processes guiding normative behaviour are important, domain-specific, and genetically inherited.…”
mentioning
confidence: 99%
“…This raises the possibility that great apes may experience at least rudimentary self-conscious emotions, too, as it has been suggested that great apes, similarly to infants and toddlers, are able to represent oneself in mind manifesting through self-recognition, perspective-taking (Krachun et al, 2019), empathy (Clay et al, 2018), and engaging in pretense (Matsuzawa, 2020). It has recently been argued that great apes may internalize social norms and rules (Fitzpatrick, 2020;van de Waal et al, 2013) and possess some forms of Theory of Mind (Krupenye and Call, 2019) giving rise to the possibility that they may experience even more complex forms of evaluative self-conscious emotions, such as shame and guilt.…”
mentioning
confidence: 99%